Echinacea biotechnology: advances, commercialization and future considerations - Jessica L. Parsons; Stewart I. Cameron; Cory S. Harris; Myron L. Smith (Taylor & Francis Group, 2018)
Context: Plants of the genus Echinacea (Asteraceae) are among the most popular herbal supplements on the market today. Recent studies indicate there are potential new applications and emerging markets for this natural health product (NHP). Objective: This review aims to synthesize recent developments in Echinacea biotechnology and to identify promising applications for these advances in the industry. Methods: A comprehensive survey of peer-reviewed publications was carried out, focusing on Echinacea biotechnology and impacts on phytochemistry. This article primarily covers research findings since 2007 and builds on earlier reviews on the biotechnology of Echinacea. Results: Bioreactors, genetic engineering and controlled biotic or abiotic elicitation have the potential to significantly improve the yield, consistency and overall quality of Echinacea products. Using these technologies, a variety of new applications for Echinacea can be realized, such as the use of seed oil and antimicrobial and immune boosting feed additives for livestock. Conclusions: New applications can take advantage of the well-established popularity of Echinacea as a NHP. Echinacea presents a myriad of potential health benefits, including anti-inflammatory, anxiolytic and antibiotic activities that have yet to be fully translated into new applications. The distinct chemistry and bioactivity of different Echinacea species and organs, moreover, can lead to interesting and diverse commercial opportunities.